Study on Surface Damage Induced by High Heavy Layer Movement and Mining-Induced Earthquakes - Zonglong Mu; Jingqi Ji; Jinglong Cao; Maoning Shi; Jiaxin Zhuang; Chunlong Jiang; Jiaxun Li (Applied Sciences, 2025)
In practice, the bending and fracturing of heavy layers is often considered the primary cause of surface damage, leading to significant environmental impacts, whereas heavy layer-type mining-induced earthquakes are frequently overlooked. This study combines theoretical analysis, UDEC numerical simulations, and industrial experiments to investigate the dynamic behavior of heavy layers and the mechanisms through which mining-induced earthquakes trigger surface damage. It aims to demonstrate that heavy layer movement and mining-induced earthquakes cause surface damage and to develop a replicable engineering solution for seismic prevention and subsidence control in heavy layer mining areas. The results reveal that surface damage stems from the synergistic effects of heavy layer fracturing and associated mining-induced earthquakes, where bending subsidence from heavy layer fracturing is the primary driver, and mining-induced earthquakes act as a secondary factor by compressing fragmented rock pores to amplify overlying layer subsidence. Industrial tests at the 7202 working face using deep-hole roof pre-splitting blasting successfully fractured the heavy conglomerate layer, enhanced goaf bulking, and reduced the intensity of layer movement. This intervention significantly decreased the frequency and energy of mining-induced earthquakes, mitigating surface damage. These findings provide a practical framework for the integrated control of mining-induced earthquakes and subsidence in heavy layer environments.